ECTOMYCORRHIZAL COLONIZATION AND GROWTH OF Anthoshorea javanica UNDER SOIL AMELIORANT TREATMENTS - Melya Riniarti (Jurnal Belantara, 2026)
Anthoshorea javanica (sin. Shorea javanica) is an ectomycorrhiza-dependent Dipterocarpaceae species whose successful nursery establishment relies on the rapid formation of functional ectomycorrhizal symbiosis. Although the Scleroderma spore inoculum is practical for large-scale nursery application, delayed spore germination may limit early seedling growth. Previous studies have mainly evaluated ectomycorrhizal species or inoculum dosage, whereas the interaction between spore-based ectomycorrhizal inoculation and soil ameliorants remains poorly understood. This study aimed to evaluate the effects of soil ameliorants on ectomycorrhizal colonization and growth of A. javanica seedlings inoculated with Scleroderma dictyosporum and Scleroderma columnare. A factorial completely randomized design was employed using two ectomycorrhizal species and three soil ameliorant treatments (control, humic acid, and Bio-Nature 50), with six replications per treatment. Growth variables and ectomycorrhizal colonization were analyzed using two-way ANOVA followed by Fisher's LSD test (P < 0.05). The interaction between ectomycorrhizal species and soil ameliorants significantly affected leaf area and shoot dry weight. The combination of S. dictyosporum and Bio-Nature 50 produced the highest leaf area (33.24 cm²) and shoot dry weight (1.80 g). Ectomycorrhizal colonization remained consistently high (79.23–91.59%) across all treatments, with no significant differences, while anatomical observations confirmed successful symbiosis through the formation of mantle and Hartig net structures. These findings demonstrate that Bio-Nature 50 enhances seedling growth responses when combined with compatible Scleroderma species without altering colonization levels. This information provides a practical basis for selecting combinations of soil ameliorants and ectomycorrhizal inoculum to improve the production of high-quality A. javanica seedlings in forest nurseries.